Aberrant lung lipids cause respiratory impairment in a Mecp2-deficient mouse model of Rett syndrome. Issue 22 (6th July 2021) - Vashi, Neeti; Ackerley, Cameron; Post, Martin; Justice, Monica J
Abstract: Severe respiratory impairment is a prominent feature of Rett syndrome, an X-linked disorder caused by mutations in methyl CpG-binding protein 2 ( MECP2 ). Despite MECP2's ubiquitous expression, respiratory anomalies are attributed to neuronal dysfunction. Here, we show that neutral lipids accumulate in mouse Mecp2- mutant lungs, whereas surfactant phospholipids decrease. Conditional deletion of Mecp2 from lipid-producing alveolar epithelial 2 (AE2) cells causes aberrant lung lipids and respiratory symptoms, whereas deletion of Mecp2 from hindbrain neurons results in distinct respiratory abnormalities. Single-cell RNA sequencing of AE2 cells suggests lipid production and storage increase at the expense of phospholipid synthesis. Lipid production enzymes are confirmed as direct targets of MECP2-directed nuclear receptor co-repressor 1/2 transcriptional repression. Remarkably, lipid-lowering fluvastatin improves respiratory anomalies in Mecp2- mutant mice. These data implicate autonomous pulmonary loss of MECP2 in respiratory symptoms for the first time and have immediate impacts on patient care.